Study of the hyperglycemic condition in diseases of liver in non-obese clinical patients - Singh, Chander Jeet; Kumar, Dinesh (Journal of Drug Delivery and Therapeutics, 2018)
Hyperglycemia is best documented by Whipple´s triad: symptoms compatible with hypoglycemia, low blood glucose concentration and alleviation of symptoms after the glucose concentration is raised. In experimental studies in healthy adults, fifteen out of the 19 patients who developed hypoglycaemia on the fasts during MT were re-tested 3 to 4 months after cessation of therapy. Fasting tolerance had improved in all of them. It had become normal in 10 out of 15 patients (67%). In 5 patients, blood glucose levels still fell below 2.7 mmol/l (range 2.0 to 2.6 mmol/l) after 16 hours of fasting. However, none had any symptoms.Keywords: Hypertension, Diabetes mellitus, Glucose, Glycolysis